1999
DOI: 10.1093/ije/28.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation designs for adequacy, plausibility and probability of public health programme performance and impact

Abstract: The question of why to evaluate a programme is seldom discussed in the literature. The present paper argues that the answer to this question is essential for choosing an appropriate evaluation design. The discussion is centered on summative evaluations of large-scale programme effectiveness, drawing upon examples from the fields of health and nutrition but the findings may be applicable to other subject areas. The main objective of an evaluation is to influence decisions. How complex and precise the evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
463
0
78

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 591 publications
(547 citation statements)
references
References 7 publications
6
463
0
78
Order By: Relevance
“…Em Montes Claros-MG, pesquisa utilizando o PCATool-versão infantil, aplicado aos cuidadores de crianças, demonstrou um escore de acesso de (5,5), inferior ao Escore Geral da APS (6,6) 18 . Kolling, em estudo de linha de base dos municípios do Telessaúde do Rio Grande do Sul, utilizando a versão profissionais do PCATool, encontrou alto grau de orientação para a APS (7,2) e baixo grau no atributo de Acesso de Primeiro Contato (5,8) 19 . Outro estudo com o PCATool, nas UBS do município de Porto Alegre, com a aplicação do PCATool versão profissionais, encontrou resultados similares 20 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Em Montes Claros-MG, pesquisa utilizando o PCATool-versão infantil, aplicado aos cuidadores de crianças, demonstrou um escore de acesso de (5,5), inferior ao Escore Geral da APS (6,6) 18 . Kolling, em estudo de linha de base dos municípios do Telessaúde do Rio Grande do Sul, utilizando a versão profissionais do PCATool, encontrou alto grau de orientação para a APS (7,2) e baixo grau no atributo de Acesso de Primeiro Contato (5,8) 19 . Outro estudo com o PCATool, nas UBS do município de Porto Alegre, com a aplicação do PCATool versão profissionais, encontrou resultados similares 20 .…”
Section: Discussionunclassified
“…Habicth et al 8 propuseram, baseados em Donabedian, que a avaliação de programas e de serviços de saúde buscasse orientar os responsáveis pela tomada de decisão (gestores em saúde). Diante de estratégias ou programas que já dispõem de evidências de plausibilidade e de probabilidade, o eixo de avaliação mais adequado para auxiliar os gestores em saúde seria a adequabilidade.…”
Section: Introductionunclassified
“…As it was nonrandomized, we can evaluate the plausibility, but not the probability that the study intervention resulted in an improved adequacy of the complementary diet (Habicht et al, 1999). Hence, we cannot establish whether some other confounding factors contributed to the difference in dietary intakes between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Retained papers underwent full-text review (performed independently by BW and LSP) to determine whether they described studies that satisfied the following criteria: subjects resided in areas where Plasmodium falciparum and Plasmodium vivax are endemic; ITN delivery at scale was evaluated; ITN ownership among households, receipt by pregnant women and/or use among children under 5 was evaluated; and an individual or cluster-randomized controlled design, a nonrandomized design, a quasi-experimental design, a beforeand-after design, an interrupted time series design or a cross-sectional design without temporal or geographical controls was used. [11][12][13] Papers meeting these criteria were termed "index papers". In addition to documenting and characterizing the strategies for delivering ITNs at scale and summarizing ITN ownership among households and ITN use among children under 5, this review also aimed to summarize the reported cost or costeffectiveness of different strategies and to synthesize information on reported factors influencing delivery of ITNs at scale.…”
Section: Eligibility Criteriamentioning
confidence: 99%